A New Framework for Information System Development on Instant Messaging for Low Cost Solution - I Made Sukarsa; I Ketut Gede Darma Putra; Nyoman Putra Sastra; Lie Jasa (Universitas Ahmad Dahlan, 2018)
The increasingly inexpensive Internet has spurred the growth of online information system services in various companies. Almost all services are available in forms on web or mobile applications. For small companies, this particular system is more difficult to implement as it requires a substantial cost allocated for hosting, domain and server devices. The solution is to develop a framework for building information system services through Instant Messaging (IM) such as Telegram, Line or XMPP / Jabber using the Design Science Research Methodology. This proposed framework has the ability to transform the existing information system services into chat services with RBAC role, session, validation and natural interaction using Indonesian-language conversations. The framework that consists of Initiate layers, business process and communication, memory group and OLTP DBMS will produce low-cost solution for the development of integrated information systems service.